Brain Mechanisms of Altered Consciousness in Generalised Seizures - Stefano Seri; Daniela Brazzo; Ngoc J. Thai; Antonella Cerquiglini (Behavioural Neurology)
In spite of the inherent difficulties in achieving a biologically meaningful definition of consciousness, recent neurophysiological studies are starting to provide some insight in fundamental mechanisms associated with impaired consciousness in neurological disorders. Generalised seizures are associated with disruption of the default state network, a functional network of discrete brain areas, which include the fronto-parietal cortices. Subcortical contribution through activation of thalamocortical structures, as well as striate nuclei are also crucial to produce impaired consciousness in generalised seizures.